Severe Cystic Periventricular Leukomalacia in a Premature Infant with Capnocytophaga Sepsis - W. Thomas Bass; Donna DeLoach; Jamil H. Khan; Glen A. Green; Kenji M. Cunnion (Thieme Medical Publishers, Inc., 2014)
Abstract Capnocytophaga is an opportunistic gram-negative anaerobic bacillus found in the oropharyngeal cavity of mammals and is associated with periodontal disease in humans. Sepsis, osteomyelitis, lung abscess, endocarditis, and meningitis have been reported in humans following animal bites. Perinatal infection with Capnocytophaga is infrequent and is generally considered to have a low risk of morbidity to the mother and fetus. We report a case of neonatal Capnocytophaga sepsis associated with the development of severe cystic periventricular leukomalacia.